Conceptual Design of Moon Lander Spacecraft - kevin, alexander; Ramadhana, A; Pardede, D C X; Koswara, S F; Abednego, J; Poetro, R E; Fathurrohim, L (FTMD Institut Teknologi Bandung, 2023)
Space exploration is important for the development of humankind such as for exploiting unlimited resources from the celestial body or making a new colony on outer space. The Moon exploration is chosen because it can be made as a base for outer space exploration. In this study, the main objective is to design a Moon lander spacecraft with a mission to take a photograph of the Indonesian flag with Earth’s globe as the background and transmit it to the ITB ground station. Designing a Moon lander spacecraft involves many engineering fields, such as aerospace, astronautics, electrical, telecommunication, etc. In this study, the design process is based on the DRO and consists of trajectory analysis, landing site and scenario, determination of launch vehicle, subsystems analysis, and cost analysis. The subsystems are limited to propulsion, payload, power, communication, and structure. The design generates a 500-kg Moon cargo lander spacecraft with a landing site on 28° latitude. The mission will take 6 days to reach the low lunar orbit of the Moon. The propulsion analysis shows that the propellant needed is 200 kg N2O4/UDMH. The resolution of the Earth’s globe is 134.3 arcseconds/pixel. The power system can provide power for 5.69 years. The spacecraft also provides 3 links to communicate between the spacecraft on the Moon and the ITB ground station. The structure’s minimum factor of safety is 1.6 with its first natural frequency in the launch vehicle being 63.66 Hz. The spacecraft’s expected cost is 220M USD. The results show that the Moon lander spacecraft can conduct such a mission based on the DRO. However, the payload subsystem needs to be re-evaluated.